Decreased haptoglobin levels inversely correlated with pulmonary artery pressure in patients with pulmonary arterial hypertension: A cross-sectional study. Issue 43 (October 2017) - Nakamura, Hiroyuki; Kato, Masaru; Nakaya, Toshitaka; Kono, Michihiro; Tanimura, Shun; Sato, Takahiro; Fujieda, Yuichiro; Oku, Kenji; Ohira, Hiroshi; Bohgaki, Toshiyuki; Yasuda, Shinsuke; Tsujino, Ichizo; et al.
Abstract : Abstract: We investigated the serum haptoglobin levels in patients with pulmonary arterial hypertension (PAH) based on the hypothesis that haptoglobin levels would reflect subclinical hemolysis due to microangiopathy in pulmonary arterioles. This cross-sectional study included 3 groups of patients attending Hokkaido University Hospital: PAH, chronic thromboembolic pulmonary hypertension (CTEPH), and connective tissue diseases (CTD) without PAH (CTD-non-PAH) group. Serum haptoglobin levels were measured by standardized turbidimetric immunoassay in all patients. Demographic data, laboratory results, right heart catheter, and echocardiographic findings were extracted from the medical records. Decreased haptoglobin levels were defined as below 19 mg/dL based on the 95th percentile of healthy controls. Thirty-five patients in PAH group including 11 with idiopathic PAH (IPAH) and 24 with CTD-associated PAH (CTD-PAH), 27 in CTEPH group, and 32 in CTD-non-PAH group were analyzed. Serum haptoglobin levels in PAH group (median 66 mg/dL) were significantly lower than those in CTEPH group (median 94 mg/dL, P  = .03) and CTD-non-PAH group (median 79 mg/dL, P  = .03). The prevalence of decreased haptoglobin levels was 26% in PAH group, 15% in CTEPH group, and 6% in CTD-non-PAH group. Serum haptoglobin levels had a significant negative correlation ( r  = −0.66, P  < .001) with mean pulmonary artery pressure in PAH group, particularly in CTD-PAH subgroup ( r  = −0.74, P  < .001), but no correlation in IPAH subgroup ( r  = −0.52, P  = .13) and in CTEPH group ( r  = −0.17, P  = .41). Follow-up cases of CTD-PAH showed lowering pulmonary artery pressure led to normalizing serum haptoglobin levels. Serum haptoglobin levels decreased in PAH patients and inversely correlated with pulmonary artery pressure in CTD-PAH patients, suggesting their potential as a surrogate marker for CTD-PAH.